PHOTOMETRIC OBSERVATIONS AND PERIOD CHANGES FOR THE THREE RR LYRAE TYPE STARS: DM CYG, V341 AQL and AV PEG - Udovichenko, S. N. (Одеські астрономічні публікації, 2007)
During observational period 2006-2007 the CCD photometric observation with V system for three RR Lyr type stars: DM Cyg, V341 Aql and AV Peg have been carried out. It was the light curves obtained and the maxima moments were determined. For the purpose of periods changes variation the graphics of O - C was plotted for long term intervals of time, containing several dozen of years, having applied the early published moments of light variations maxima. From these data the new elements for determine of light variations maxima was calculated.